A New Approach to the Study of Bound Residues in Plants; Incorporation of Tritium-Labeled 3-Phenoxybenzoic Acid into Cell Wall Components of Cypress - FUJISAWA, Takuo (Journal of Pesticide Science, 2002)
「INTRODUCTION」 To evaluate the bioavailability of a pesticide incorporated into plant cell walls as bound residues, 1) it is necessary to know the binding mechanism of pesticide with plant macromolecules, i.e., lignin, hemicellulose and cellulose. Despite a number of reviews1-5) on the features of pesticides as bound residues, their existing form in plants is still not well understood. Typically, bound residues have been analyzed by treating macerated whole plants with various solvent systems to demolish the macromolecules and solubilising the bound residues. However, interpretation of the results was sometimes extremely confusing because macerated plant contains various types of cells. Furthermore, the ability of a solvent to reach the place where bound residues exists can vary, having a tremendous impact on the accuracy of selectivity when solubilising the target macromolecule. Bound residues have also been studied using plant cell cultures. 6) However, such an approach does not consider the pesticide incorporated into secondary cell walls.